Impact of obstructive sleep apnea on assisted ventilation in children with asthma exacerbation. Issue 5 (11th January 2021) - Tsou, Po‐Yang; Cielo, Christopher; Xanthopoulos, Melissa S.; Wang, Yu‐Hsun; Kuo, Pei‐Lun; Tapia, Ignacio E.
Abstract: Objective: To determine the impact of obstructive sleep apnea (OSA) on asthma exacerbation severity in children hospitalized for asthma exacerbation. Hypothesis: OSA is associated with greater use of invasive mechanical ventilation (IMV) and noninvasive mechanical ventilation (NIMV) in children hospitalized for asthma exacerbation. Study Design: A retrospective cohort study. Patient–Subject Selection: Hospitalization records of children aged 2–18 years admitted for acute asthma exacerbation were obtained for 2000, 2003, 2006, 2009, and 2012 from the Kids' Inpatient Database. Methodology: The primary exposure was OSA, the primary outcome was IMV, and secondary outcomes were NIMV, length of hospital stay (LOS), and inflation‐adjusted cost of hospitalization. Multivariable logistic regression, negative binomial, and linear regression were conducted to ascertain the impact of OSA on primary and secondary outcomes. Exploratory analyses investigated the impact of obesity on primary and secondary outcomes. Results: Among 564, 467 hospitalizations for acute asthma exacerbation, 4209 (0.75%) had OSA. Multivariable regression indicated that OSA was associated with IMV (adjusted odds ratio [OR], 5.33 [95% confidence interval, CI: 4.35–6.54], p < .0001), NIMV (adjusted OR, 8.30 [95% CI: 6.56–10.51], p < .0001), longer LOS (adjusted incidence rate ratio, 1.34 [95% CI 1.28–1.43], p < .0001), and greater inflation‐adjusted cost of hospitalization (adjusted β, 0.38 [95% CI: 0.33–0.43], p < .0001). Obesity was also significantly associated IMV, NIMV, longer LOS, and greater inflation‐adjusted cost of hospitalization. There was no interaction between OSA and obesity. Conclusion: OSA is an independent risk factor for IMV, NIMV, longer LOS, and elevated inflation‐adjusted costs of hospitalization in children hospitalized for asthma exacerbation.